SM-ND ISOTOPIC SYSTEMATICS OF THE KURUMKAN SUBGROUP, THE IENGRA GROUP OF ALDAN SHIELD - Kovach V.P.; Kotov A.B.; Salnikova E.B.; Zagornaya N.Yu.; Berezkin V.I.; Smelov A.P. (My University, 1996)
The first data on the Nd isotopic composition in high-AI gneisses and associated gamet-hypersthene-biotite plagiogneisses of the Kurumkan Subgroup, the lengra Group of Aldan Shield are presented. The obtained results show that rocks of the subgroup accumulated after ∼2.9 Ga, i.e., during the Late Archean or Early Proterozoic, and not the Early Archean evolutionary stage of the shield. Protoliths of garnet-hypersthenebiotite gneisses were not older than 2.3 Ga, and their formation marks the Early Proterozoic stage of continental crust generation in the Aldan granulite-gneiss region.
Keywords: Archean; Proterozoic; Precambrian::Archean; Precambrian::Proterozoic; Докембрий::Архей; Докембрий::Протерозой